APPLICATION OF PROBLEM BASED LEARNING LEARNING MODELS TO IMPROVE CRITICAL THINKING ABILITY AND LEARNING ACHIEVEMENT - Lia Susanti; Bambang Sahono (UNIB Press, 2019)
The purpose of this study is to describe the application of problem based learning learning models to improve critical thinking skills and learning achievement. The design of this study is classroom action research consisting of three cycles. Each cycle consists of planning, action, observation and reflection. Respondents in the study numbered 25 students consisting of 15 men and 10 women. Data collection using sheets and test. observation sheets with 7 assessed aspects, identify problems according to information obtained, comparing similarities and differences of opinion in group discussions, raise relevant and regular question, express opinion in freely and responsibly, assessing the impact of an event, being able to explain problems and make simple conclusions, reflect the value of an event. Analysis of the data used is the average rat (mean) and tests. The results showed that the application of the problem based learning model of learning can improve critical thinking skills and student achievement. the application of problem based learning can be used in other subjects